Electric field-driven fabrication of anisotropic hydrogels from plant proteins: Microstructure, gel performance and formation mechanism. (March 2023) - Cao, Mengmeng; Liao, Li; Zhang, Xingcai; Chen, Xing; Peng, Shengfeng; Zou, Liqiang; Liang, Ruihong; Liu, Wei
Abstract: Soy protein isolate (SPI) hydrogels with anisotropic structures were fabricated under a low voltage electric field (1.5 V/cm) and different levels of NaCl (100–500 mmol/L). Under the weak direct-current electric field, the negatively charged protein molecules orderly arranged and accumulated around the positive electrode, where the surface charges of the amino acids were screened by the local H + and added ions. Meanwhile, the random coil in the protein secondary structure disappeared to form ordered structures ( α -helix and β -turn), and the protein exposed more hydrophobic and sulfhydryl groups. Intermolecular interactions, including disulfide bonds, hydrogen bonds and hydrophobic interactions facilitated the cross-linking of protein molecules to form hydrogels. All the hydrogels showed anisotropic networks, and the fraction of SPI attached to the gel phase (36.80% ∼ 62.17%) was found to increase with the rise of NaCl level in the protein solution. Moreover, the hardness (96.13–210.54 g), springiness (33.88% ∼ 68.30%), chewiness (121.59–292.12 g⋅s) and swelling resistance (142.79% ∼ 54.20%) of electrogels were all enhanced with increased NaCl level. Conversely, a higher ionic strength compromised the water holding stability (99.62% ∼ 66.75%) of electrogels, which could be attributed to the increased pore size within their networks that allowed moisture to be transferred. These findings may provide a novel insight for design and fabrication of plant protein hydrogels with desirable structures and characters through a green and sustainable approach. Graphical abstract: Image 1 Highlights: Soy protein isolate hydrogels were fabricated under a low voltage electric field. Electric fields promoted the structural transition of soy proteins to form more ordered structures. Soy proteins were directionally arranged under electric fields to generate anisotropic structures. Higher NaCl levels contributed to thicker strands and coarse pores within the hydrogel networks. Higher NaCl levels enhanced the texture and swelling resistance of hydrogels, but weakened their water holding stability.